A review and meta-analysis of the efficacy of arbuscular mycorrhizal fungi in remediating toxic metals in mine-affected soils - Banerjee, Sonali; Mandal, Jajati; Sarkar, Dibyendu; Datta, Rupali; Bhattacharyya, Pradip (Frontiers in Environmental Science, 2025)
Mines are natural reservoirs of various minerals, metals, and metalloids. Several heavy metals (HMs), such as Pb, Cd, Cr, Cu, and Ni, are major anthropogenic pollutants that cause severe environmental pollution. The accumulation of these toxic HMs in soils has raised several concerns for crop growth, food safety, and marketing. Physiological and biochemical processes in plants are severely impacted by HMs, disrupting normal metabolic activities and reducing biomass production. Phytoremediation plays a pivotal role in addressing HM contamination by offering an eco-friendly, economical, and holistic solution. Similarly, arbuscular mycorrhizal fungi (AMF) play a significant role by forming a symbiotic relationship with plant roots. In this association, plants provide root exudates, while AMF enhance plant growth under heavy metal stress by supplying essential nutrients, minerals, and water. These fungi also improve nutrient status, soil quality, and ecosystem stability. The present review and meta-analysis encompass an examination of the global distribution of toxic HMs in mining-affected areas. Furthermore, the study highlights the role of various plant species and microbes, particularly AMF, in mitigating HM stress and its impact on plant growth and nutrition. The meta-analysis also evaluates the efficacy of AMF as a remediation strategy for HM-impacted mine soils.